High-flow nasal cannula in nonlaser microlaryngoscopic surgery: a prospective study of 19 cases in a chinese population - Bo Ma; Fei Liu; Dandan Wang; Ruihan Zhong; Kaihao Lin; Shuo Li; Jie Zhang; Chaoyang Li (BMC Anesthesiology, 2022)
Abstract Background High-flow nasal cannula (HFNC) is a new type of oxygen therapy, but its application in surgery remains unclear, we tried to describe the application of HFNC in microlaryngoscopic surgery for the Chinese population. Methods Nineteen adults, American society of anesthesiology class (ASA) 1–2 patients with body mass index < 30 kg.m−2 underwent microlaryngoscopic surgery using HFNC for airway management. Outcomes included apnoea time, intraoperative oxygenation, carbon dioxide value, lactate value, and the relationship between the duration of apnoea time and carbon dioxide levels. Results A total of 19 patients underwent vocal cord tumor resection under a microlaryngoscope with HFNC as the sole method of ventilation. The mean age was 39.7 years old, and the mean BMI was 23.9 kg.m−2. The mean apnea time was 21.5 min. The SpO2 of 18 patients remained above 90%, and only 1 patient dropped to 88%. The average basal lactate and highest lactate value was 0.58 mmol. L−1 and 0.68 mmol.L−1. The difference between basal and highest lactate values was statistically significant (P < 0.05). The average highest PaCO2 value was 79.4 mmHg. The PaCO2 increased by 1.68 ± 0.12 mmHg every minute linearly. Conclusions In the case series we have observed that HFNC would be safe and effective oxygenation and ventilation technique for selected Chinese patients undergoing non-laser microlaryngoscopic surgery within 30 min. The tubeless technology reduces the complications of tracheal intubation and jet ventilation and clears the surgical field of vision. Trial registration Chinese Clinical Trial Registry ( ChiCTR100049144 ).